Practice Patterns of Graduates of a Rural Emergency Medicine Training Program - Dylan S. Kellogg; Miriam S. Teixeira; Michael Witt (Western Journal of Emergency Medicine)
Introduction: Rural communities continue to face a shortage of emergency physicians despite the growing number of emergency medicine (EM) residencies. In rural areas, emergency physicians tend to be older, male, and White, and are less likely to have completed EM residency training or have board certification. There is also currently a higher rate of rural physicians leaving clinical practice than in urban emergency departments (ED). In this cross-sectional study we sought to identify the work environments of graduates of a rural EM residency program, and the strengths and weaknesses of such a program. Methods: We conducted a survey among 29 graduates of a community-based EM program to evaluate the effectiveness of a residency program in training physicians who will work in rural areas. The survey assessed the graduates’ perceptions of their level of preparedness, further training, and practice location after completing the program. Results are reported using descriptive statistics. Results: Twenty respondents completed the survey (69%). Most of them identified as male (60%), White (70%), and non-Hispanic or -Latino (80%). Seventy-five percent of the graduates work in counties with fewer than 1,000,000 inhabitants, and 70% work in community hospitals and EDs caring for fewer than 100,000 patients/year. Four (20%) declared to work in critical access hospitals. Overall, respondents felt confident in their residency training. Conclusion: A community-based EM training program may be an effective strategy for producing emergency physicians who go on to work in rural and smaller communities.